(untitled) (Alternautas, 2023)
This article explores how the Aikanã, speakers of an isolate language, who live in the south-eastern Amazon, in the Brazilian State of Rondônia, make sense of the drastic transformations brought about by the colonisation of this region. Through an analysis of Aikanã narratives and life histories, the article highlights how Aikanã social memory gives meaning to experiences of contact, land loss and environmental destruction. It will contemplate the temporal markers, i.e. periodisations that occur in narratives and life histories and that delineate Aikanã historicity. These temporal markers refer predominantly to an experienced past between the beginning of the 20th century and the present, from a distant period of displacement from their traditional territory and the severe loss of human lives to the transformation of the forest into pastures for cattle and soy. In this vein, temporal markers are also anchored in space, unveiling sentiments of nostalgia and ecological grief for a past fertility of social life, interconnected with the fertility of the more-than-human world of the lost forest. Exploring Aikanã narrativity and its operation in the construction of social memory, the article aims to contribute to contemporary debates on Amazonian historicities, as well as to the theoretical and political role of Amazonian socialities in face of the current environmental crisis.